FRAMEWORK ON CRITICAL THINKING IN THE TECHNOLOGICAL ASSESSMENT AND UTILIZATION ON EDUCATION FOR CITIZENS (Proceedings of the International Conference on Education, 2025)
The development of competencies has been emphasized globally, with critical thinking increasingly recognized as a key competency. The importance of it has been discussed in Japan, taking up such issues in judgment of technology assessment and control as the nuclear power plant accident. Such risk literacy questions the educational literacy for the use of the scientific and technological systems, and is considered to be an important contemporary issue concerning technological assessment and utilization handled in technology education. This study was extracted the characteristics of thinking included in the critical thinking process and analyzed the teaching contents for technological assessment and utilization and use based on the critical thinking processes. Using perspectives proposed by Ennis and Kusumi, this study extracted elements of critical thinking processes found within these contents and organized the thinking process in the teaching contents for technological assessment and utilization from the viewpoint of critical thinking processes. The results showed that the critical thinking processes were characterized the thinking to focus the discussion, to examine the information source as a premise for inference, to make inductive, deductive, and value judgments based on multiple facts and grounds and to derive the conclusion of the discussion from the process so far. Furthermore, it was suggested that it's important to teach decision-making based on the critical thinking process, combining forward thinking and reflective thinking for fostering the competencies of technological assessment and utilization. This study targets the important theme of how to deal with the technology of installing and operating artifacts such as the nuclear power plant accidents. It also shows significance that structurally demonstrates the critical thinking necessary for each citizen to assess and utilize technology in a future society where technology continues to develop by leaps and bounds.
Keywords: Critical Thinking; Competences of Technological Assessment and Utilization; Thinking Processes; Teaching Contents; Technology Education